Causes of Low Absorption of Local Workers to Labor Fulfillment in Indonesia - Pratama Herry Herlambang; Suwinda, Suwinda; Muhammad Habiby Abil Fida Safarin (The Indonesian Journal of International Clinical Legal Education, 2024)
This study aims to identify the factors contributing to the low absorption of local workers in Indonesia, focusing on the skills gap, the impact of digital transformation, and the effectiveness of labor policies. The methodology employed is qualitative, utilizing interviews, questionnaires, and literature reviews. The results indicate that the skills gap between the local workforce and the requirements of modern industries is a significant issue, as many workers lack skills relevant to market demands. Furthermore, rapid digital transformation has caused disruptions across various sectors, yet the local workforce’s readiness to adapt remains low. Government initiatives, such as the Pre-Employment Card Program, have not been entirely effective in upskilling the local workforce, and competition with foreign workers exacerbates this problem. This study recommends enhancing the education and training system to better align with industry needs, increasing access to quality training programs, and developing policies that support local skills development. These findings are expected to contribute to the formulation of more effective and sustainable labor policies in Indonesia.